Phylogenetic networks : concepts, algorithms and applications - Huson, Daniel H.; Rupp, Regula; Scornavacca, Celine (Cambridge : Cambridge University Press, 2010)
"In the first part of this book we give an introduction to basic concepts from graph theory and systematics (Chapter 1). We briefly discuss the problem of aligning molecular sequences (Chapter 2) and give a more detailed introduction to the computation of phylogenetic trees from aligned sequences and distances (Chapter 3). Finally, we give a brief introduction to the computation of phyloge-netic networks, which also serves as an overview for the material presented in the second and third parts of the book (Chapter 4). Chapters 2 and 3 are provided for the sake of completeness and reference. They can be skipped by readers who have a basic knowledge of phylogenetic "
1. Basics -- 2. Sequence alignment -- 3. Phylogenetic trees -- 4. Introduction to phylogenetic networks -- 5. Splits and unrooted phylogenetic networks -- 6. Clusters and rooted phylogenetic networks -- 7. Phylogenetic networks from splits -- 8. Phylogenetic networks from clusters -- 9. Phylogenetic networks from sequences -- 10. Phylogenetic networks from distances -- 11. Phylogenetic networks from trees -- 12. Phylogenetic networks from triples or quartets -- 13. Drawing phylogenetic networks -- 14. Software
Includes bibliographical references (p. 343-357 ) and index
Keywords: Cladistic analysis -- Data processing; Cladistic analysis -- Mathematics; Phylogeny